Mechanical Ventilation in Non Lung-Post Surgery Patients - Ika Yunita Sari; Sri Wening Pamungkasningsih; Menaldi Rasmin (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
A case of a 41-year-old man, with a lump in his left abdomen since 5 months before admission to the hospital. In the last 2 weeks the patient complained of reddish urine and pain during urination. The diagnosis of the patient is a left kidney tumor, has performed nephrectomy and splenectomy surgery. Postoperative complications include sepsis, anemia and hypoalbuminemia. Sepsis in these patients is caused by colonic perforation leading to intra-abdominal infection. These complications cause patients to get treatment in the intensive care unit longer by using a ventilator for four days.